Sustainable ecotourism in desert areas in Iran: potential and issues - Mahdi Eshraghi; Mohd Ekhwan Toriman; Habibah Ahmad (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2010)
Desert areas are no longer left unattempted in tourism developments. Varieties formation of natural assets provides a spectrum of attraction to many segments of tourists, especially to nature lovers and adventure ecotourists. Broad and white salt plains, golden dunes as well as light green, yellow and red hilly areas make a wonderful spectrum of worth seeing colors for desert tourists in daylight. In fact, a variety form of natural formation such as desert forms (of wind and water erosion), special flora and fauna and beautiful panoramas are among many wonders to natural ecotourists. All the above attractions, if managed properly may provide positive impacts on local communities residing surrounding some of the areas. However, the benefits of sustainable ecotourism in desert areas in Iran are seldom been explored and studied. This study based on latest information and data has conducted in the first half of 2010 during the desert tourism season in Iran.The study indicates that desert tourism helps to create a sustainable employment for the local people and increases gross production as well as preserves valuable plant and animal species, cult. This article aims to explore the benefits of desert tourism in Iran for the local community as well as for the country heritage and stabilizes society institution at the macro levels. This article also tries to identify issues of desert ecotourism including over pressurred on natural resources. This pressure takes the form in particular of overexploitation of land resources, and the excessive clearing and harvesting of land cover. The results are diminished crop yield, polluted streams and groundwater. The article concludes with suggestions of a holistic way of developing natural attractions for sustainable desert ecotourism in Iran